MicroRNA-Related Strategies to Improve Cardiac Function in Heart Failure - Zhou, Huatao; Tang, Weijie; Yang, Jinfu; Peng, Jun; Guo, Jianjun; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2021)
Heart failure (HF) describes a group of manifestations caused by the failure of heart function as a pump that supports blood flow through the body. MicroRNAs (miRNAs), as one type of non-coding RNA molecule, have crucial roles in the etiology of HF. Accordingly, miRNAs related to HF may represent potential novel therapeutic targets. In this review, we first discuss the different roles of miRNAs in the development and diseases of the heart. We then outline commonly used miRNA chemical modifications and delivery systems. Further, we summarize the opportunities and challenges for HF-related miRNA therapeutics targets, and discuss the first clinical trial of an antisense drug (CDR132L) in patients with HF. Finally, we outline current and future challenges and potential new directions for miRNA-based therapeutics for HF.